PENGELOLAAN BADAN USAHA MILIK DESA STUDI DI DESA WARISA KAMPUNG BARU KECAMATAN TALAWAAN KABUPATEN MINAHASA UTARA. - PUSUNG, REFEN; RORONG, ARIE; TAMPONGANGOY, DEYSI (JURNAL ADMINISTRASI PUBLIK, 2022)
Realizing a just prosperous and prosperous society is the government's goal which continues tobe pursued to this day. This can be seen clearly from the authority given to villages in the formation ofVillage-Owned Enterprises to improve the village economy, increase village income, improve villagepotential management according to community needs and become the backbone of rural economic growthand equity. The purpose of this study is to find out how the Management of Village-Owned Enterprises inWarisa Village, Kampung Baru, Talawaan District, North Minahasa Regency. The research method usedis qualitative research. Informants in research are people who can provide information about research.The research focus is seen from indicators according to Ahmad Nur Ihsan and Budi Setiono focused onavailable resources, community participation and empowerment, government support and collaborationwith third parties. Data collection techniques through observation, interviews and documentation. Theresults of the study show that in practice it appears that the businesses managed by the BERSEHATIVillage-Owned Enterprises in the Village have not been able to achieve their vision and mission, especiallyin developing community economic enterprises. As a result, the management of BERSEHATI Village-Owned Enterprises looks like it is running in place and is only used as a complement to the requirementsfor receiving Village Funds as a condition for villages that will receive Village Fund assistance.Keywords : Management, Village Owned Enterprises